Immune and non-immune mediators in the fibrosis pathogenesis of salivary gland in Sjögren’s syndrome - Ma, Danbao; Feng, Yun; Lin, Xiang (Frontiers in Immunology, 2024)
Sjögren's syndrome (SS) or Sjögren's disease (SjD) is a systemic autoimmune disease clinically manifested as sicca symptoms. This disease primarily impacts the functionality of exocrine glands, specifically the lacrimal and salivary glands (SG). SG fibrosis, an irreversible morphological change, is a severe consequence that occurs in the later stages of the disease due to sustained inflammation. However, the mechanism underlying SG fibrosis in SS remains under-investigated.Glandular fibrosis may arise from chronic sialadenitis, in which the interactions between infiltrating lymphocytes and epithelial cells potentially contributes to fibrotic pathogenesis. Thus, both immune and non-immune cells are closely involved in this process, while their interplays are not fully understood. The molecular mechanism of tissue fibrosis is partly associated with an imbalance of immune responses, in which the transforming growth factor-beta (TGF-β)-dependent epithelialmesenchymal transition (EMT) and extracellular matrix remodeling are recently investigated. In addition, viral infection has been implicated in the pathogenesis of SS. Viral-specific innate immune response could exacerbate the autoimmune progression, resulting in overt inflammation in SG.Notably, post-COVID patients exhibit typical SS symptoms and severe inflammatory sialadenitis, which are positively correlated with SG damage. In this review, we discuss the immune and nonimmune risk factors in SG fibrosis and summarize the evidence to understand the mechanisms upon autoimmune progression in SS.